Analisis Konseptual tentang Peran Kecerdasan Interpersonal dalam Pembelajaran Ditinjau dari Perspektif Al-Qur’an dan Hadis: Penelitian - Ahmad, Arbi Salam; Deliani, Nurfarida; Batubara, Juliana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to conceptually analyze the role of interpersonal intelligence in learning from the perspective of the Qur’an and Hadith. Interpersonal intelligence is defined as the ability to understand, empathize with, and appropriately respond to others’ feelings and behaviors to create harmonious social relationships. In the context of education, this intelligence plays an essential role in fostering positive interactions between teachers and students and in creating a conducive learning environment. This research employs a qualitative approach using the library research method by analyzing educational psychology literature, Qur’anic exegesis, and Hadith sources. The analysis was carried out descriptively and analytically to integrate theories of interpersonal intelligence with Qur’anic and Prophetic values. The findings indicate that interpersonal intelligence is reflected in four key verses: QS. Al-Hujurat [49]:10 on brotherhood, QS. Ali Imran [3]:159 on gentleness, QS. An-Nisa [4]:36 on kindness toward others, and QS. Al-Mujadilah [58]:11 on respect for knowledge. Furthermore, the Hadiths of the Prophet Muhammad (peace be upon him) emphasize empathy, compassion, and mutual respect in social relations. Thus, interpersonal intelligence has a strong theological foundation in Islam and plays a vital role in realizing a humanistic and Qur’an-based learning process.